CAPTAIN: geração de diários de bordo digitais usando anotação contextual e conteúdo multimídia - Braga, Reinaldo B.; Martin, Hervé; Viana, Windson; Andrade, Rossana M. C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
Context-aware and multimedia systems emerge as a new application domain for smartphones thanks to the addition of sensors, user data and multimedia functionalities to these devices. To illustrate this new application domain, we present CAPTAIN: a Context-Aware and Photo-based Tool for logbook generAtIoN. CAPTAIN merges three main mechanisms: i) sensor data acquisition and multimedia creation on the mobile device, ii) a validation tool, iii) and an automatic Web-content generator. The paper also describes a user evaluation of CAPTAIN made by a real crew during the ZeroCO2 project.